Determining the Usefulness of Land Information Management System (LIMS) in Ending Land Disputes in Zimbabwean A1 Farms - Agnes, Makomo; Masarira T.P (CV. Literasi Indonesia, 2024)
This study sought to determine the usefulness of the Land Information Management System (LIMS) for the resolution of Land Disputes in Marondera District A1 resettlement areas. The research was inspired by the continued occurrence of land disputes in Marondera A1 Farms. The main thrust of the research was to determine to assess the usefulness of the LIMS model in ending land disputes in Marondera District A1 farms. The study adopted a mixed research approach hinged on pragmatism research philosophy. A cross-sectional survey research design was used. The research used stratified random sampling for quantitative data whilst purposive sampling was used for the collection of qualitative data. Structured questionnaires and interview guides were the two major instruments that were used. A sample size of 373 participants was drawn from the Department of Lands Marondera, the Zimbabwe Lands Commission, Extension officers, and A1 farmers in areas of Wenimbi, Mushandira, and Ruware in Marondera. The sample size was arrived at using the Raosoft sample size calculator. The sample size for qualitative data was not predetermined but was arrived at using the saturation principle. In the analysis of quantitative data, tables, descriptive statistics, and inferential statistics were produced using Statistical Package for the Social Sciences (SPSS) version 23. The presentation of qualitative data followed a thematic approach in which responses were shown using word cloud analysis. The study revealed that the improved LIMS will enable land registration, land use planning, land dispute resolution, and data analysis and reporting. It was recommended in the study that the government encourage open communication and collaboration among local communities, farmers, and authorities to address grievances and prevent conflicts, fostering a sense of shared responsibility and ownership. Also with LIMS government conducts a thorough audit to identify and resolve issues related to land ownership, boundaries, and usage, helping to prevent future disputes.